Biallelic variants in HPDL, encoding 4-hydroxyphenylpyruvate dioxygenase-like protein, lead to an infantile neurodegenerative condition. - Ghosh, Shereen G; Lee, Sangmoon; Fabunan, Rudy; Chai, Guoliang; Zaki, MAH S; Abdel-Salam, Ghada; Sultan, Tipu; Ben-Omran, Tawfeg; Alvi, Javeria Raza; McEvoy-Venneri, Jennifer; Stanley, Valentina; Patel, Aakash; et al. (Genet Med, 2021)
PURPOSE: Dioxygenases are oxidoreductase enzymes with roles in metabolic pathways necessary for aerobic life. 4-hydroxyphenylpyruvate dioxygenase-like protein (HPDL), encoded by HPDL, is an orphan paralogue of 4-hydroxyphenylpyruvate dioxygenase (HPD), an iron-dependent dioxygenase involved in tyrosine catabolism. The function and association of HPDL with human diseases remain unknown. METHODS: We applied exome sequencing in a cohort of over 10,000 individuals with neurodevelopmental diseases. Effects of HPDL loss were investigated in vitro and in vivo, and through mass spectrometry analysis. Evolutionary analysis was performed to investigate the potential functional separation of HPDL from HPD. RESULTS: We identified biallelic variants in HPDL in eight families displaying recessive inheritance. Knockout mice closely phenocopied humans and showed evidence of apoptosis in multiple cellular lineages within the cerebral cortex. HPDL is a single-exonic gene that likely arose from a retrotransposition event at the base of the tetrapod lineage, and unlike HPD, HPDL is mitochondria-localized. Metabolic profiling of HPDL mutant cells and mice showed no evidence of altered tyrosine metabolites, but rather notable accumulations in other metabolic pathways. CONCLUSION: The mitochondrial localization, along with its disrupted metabolic profile, suggests HPDL loss in humans links to a unique neurometabolic mitochondrial infantile neurodegenerative condition.
Keywords: 4-Hydroxyphenylpyruvate Dioxygenase; Animals; Dioxygenases; Exons; Mice; Mice, Knockout; Phenotype

Bi-allelic GAD1 variants cause a neonatal onset syndromic developmental and epileptic encephalopathy. - Chatron, Nicolas; Becker, Felicitas; Morsy, Heba; Schmidts, Miriam; Hardies, Katia; Tuysuz, Beyhan; Roselli, Sandra; Najafi, Maryam; Alkaya, Dilek Uludag; Ashrafzadeh, Farah; Nabil, Amira; Omar, Tarek; et al. (Brain, 2020)
Developmental and epileptic encephalopathies are a heterogeneous group of early-onset epilepsy syndromes dramatically impairing neurodevelopment. Modern genomic technologies have revealed a number of monogenic origins and opened the door to therapeutic hopes. Here we describe a new syndromic developmental and epileptic encephalopathy caused by bi-allelic loss-of-function variants in GAD1, as presented by 11 patients from six independent consanguineous families. Seizure onset occurred in the first 2 months of life in all patients. All 10 patients, from whom early disease history was available, presented with seizure onset in the first month of life, mainly consisting of epileptic spasms or myoclonic seizures. Early EEG showed suppression-burst or pattern of burst attenuation or hypsarrhythmia if only recorded in the post-neonatal period. Eight patients had joint contractures and/or pes equinovarus. Seven patients presented a cleft palate and two also had an omphalocele, reproducing the phenotype of the knockout Gad1-/- mouse model. Four patients died before 4 years of age. GAD1 encodes the glutamate decarboxylase enzyme GAD67, a critical actor of the γ-aminobutyric acid (GABA) metabolism as it catalyses the decarboxylation of glutamic acid to form GABA. Our findings evoke a novel syndrome related to GAD67 deficiency, characterized by the unique association of developmental and epileptic encephalopathies, cleft palate, joint contractures and/or omphalocele.
Keywords: Abnormalities, Multiple; Epileptic Syndromes; Female; Glutamate Decarboxylase; Humans; Infant, Newborn; Male; Mutation; Pedigree

A combined immunodeficiency with severe infections, inflammation, and allergy caused by ARPC1B deficiency. - Volpi, Stefano; Cicalese, Maria Pia; Tuijnenburg, Paul; Tool, Anton T J; Cuadrado, Eloy; Abu-Halaweh, Marwan; Ahanchian, Hamid; Alzyoud, Raed; Akdemir, Zeynep Coban; Barzaghi, Federica; Blank, Alexander; Boisson, Bertrand; et al. (J Allergy Clin Immunol, 2019)

Biallelic variants in KIF14 cause intellectual disability with microcephaly. - Makrythanasis, Periklis; Maroofian, Reza; Stray-Pedersen, Asbjørg; Musaev, Damir; Zaki, Maha S; Mahmoud, Iman G; Selim, Laila; Elbadawy, Amera; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Gambin, Tomasz; Sorte, Hanne S; et al. (Eur J Hum Genet, 2018)
Kinesin proteins are critical for various cellular functions such as intracellular transport and cell division, and many members of the family have been linked to monogenic disorders and cancer. We report eight individuals with intellectual disability and microcephaly from four unrelated families with parental consanguinity. In the affected individuals of each family, homozygosity for likely pathogenic variants in KIF14 were detected; two loss-of-function (p.Asn83Ilefs*3 and p.Ser1478fs), and two missense substitutions (p.Ser841Phe and p.Gly459Arg). KIF14 is a mitotic motor protein that is required for spindle localization of the mitotic citron rho-interacting kinase, CIT, also mutated in microcephaly. Our results demonstrate the involvement of KIF14 in development and reveal a wide phenotypic variability ranging from fetal lethality to moderate developmental delay and microcephaly.
Keywords: Child; Child, Preschool; Female; Humans; Intellectual Disability; Kinesin; Loss of Function Mutation; Microcephaly; Mutation, Missense; Oncogene Proteins; Pedigree; Phenotype; Protein Domains; Syndrome